Acoustic Scattering of 3D Complex Systems Having Random Rough Surfaces by Scalar Integral Equations - Juan Antonio GUEL-TAPIA; Francisco VILLA-VILLA; Alberto MENDOZA-SUÁREZ; Héctor PÉREZ-AGUILAR (Archives of Acoustics, 2016)
We propose a numerical surface integral method to study complex acoustic systems, for interior and exterior problems. The method is based on a parametric representation in terms of the arc’s lengths in curvilinear orthogonal coordinates. With this method, any geometry that involves quadric or higher order surfaces, irregular objects or even randomly rough surfaces can be considered. In order to validate the method, the modes in cubic, spherical and cylindrical cavities are calculated and compared to analytical results, which produced very good agreement. In addition, as examples, we calculated the scattering in the far field and the near field by an acoustic sphere and a cylindrical structure with a rough cross-section.